Ascorbic Acid-Induced Photosynthetic Adaptability of Processing Tomatoes to Salt Stress Probed by Fast OJIP Fluorescence Rise - Chen, Xianjun; Zhou, Yan; Cong, Yundan; Zhu, Pusheng; Xing, Jiayi; Cui, Jinxia; Xu, Wei; Shi, Qinghua; Diao, Ming; Liu, Hui-ying (Frontiers in Plant Science, 2021)
In this study, the protective role of exogenous ascorbic acid (AsA) on salt-induced inhibition of photosynthesis in processing tomatoes seedlings under salt stress has been investigated. Plants under salt stress (NaCl, 100 mmol·L-1) were foliar-sprayed with AsA (0.5 mmol·L-1), Lycorine (LYC, 0.25 mmol·L-1, an inhibitor of key AsA synthesis enzyme l-galactono-γ-lactone dehydrogenase activity) or AsA plus LYC. The effects of AsA on fast OJIP fluorescence rise curve and JIP parameters were then examined. Our results demonstrated that applying exogenous AsA significantly changed the composition of O-J-I-P fluorescence transients in plants subjected to salt stress both with and without LYC. An increase in basal fluorescence (Fo) and a decrease in maximum fluorescence (Fm) was observed. Lower K- and L-band and higher I-band were detected on OJIP transient curves compared respectively to salt-stressed plants without and with LYC. AsA application also significantly increased the values of normalized total complementary area (Sm), relative variable ﬂuorescence intensity at the I-step (VI), absorbed light energy (ABS/CSm), excitation energy (TRo/CSm) and reduction energy entering the electron transfer chain beyond QA (ETo/CSm) per reaction centre (RC) and electron transport flux per active RC (ETo/RC), while decreasing some others like the approximated initial slope of the fluorescence transient (Mo), relative variable ﬂuorescence intensity at the K-step (VK), average absorption (ABS/RC), trapping (TRo/RC), heat dissipation (DIo/RC) per active RC and heat dissipation per active RC (DIo/CSm) in presence or absence of LYC. These results suggested that exogenous AsA counteracted salt-induced photoinhibition mainly by modulating the endogenous AsA level and redox state in the chloroplast to promote chlorophyll synthesis and alleviate the damage of oxidative stress to photosynthetic apparatus. AsA can also raise the efficiency of light utilization as well as excitation energy dissipation within the photosystem II (PSII) antennae, thus increasing the stability of PSII and promoting the movement of electrons among PS1 and PSII in tomato seedling leaves subjected to salt stress.